Recent Advances on Electrolysis for Simultaneous Generation of Valuable Chemicals at both Anode and Cathode - Li, Rui; Xiang, Kun; Peng, Zhikun; Zou, Yuqin; Wang, Shuangyin (Advanced energy materials, 2021)
To make efficient use of electrical energy in the whole electrocatalysis conversion process, the integrating of anode and cathode reactions plays a vital role. The combination of electrocatalytic anodic oxidation with cathodic reduction can not only maximize the return of energy investment, but also produces value‐added materials on both sides. Herein, in this review, recent advances in co‐electrolysis processes for valuable chemical production are systematically summarized. To be more specific, the popular hydrogen evolution reaction, carbon dioxide reduction reaction, nitrogen reduction reaction as well as nitrate reduction reaction integrated with anodic oxidation reactions to value‐added products, respectively are comprehensively reviewed, and then other paired electrolysis systems (especially for biomass‐based compounds) toward high‐value‐added chemical generation are discussed in detail. This review sheds light on the integration of electrocatalytic reductions and oxidation reactions to develop high‐value substances. To benefit researchers and facilitate the progress in this field, the challenges and future prospects for these integrated reactions are also proposed. Simultaneous electrolysis processes can produce value‐added chemicals and significantly reduce operating costs. This review discusses recent advances in valuable chemical co‐generation from electrocatalytic integrating systems, involving cathodic reduction reactions (hydrogen evolution reaction, carbon dioxide, nitrogen, and nitrate reduction reaction, etc.) integrated with anodic oxidation reactions (alcohol, amine, and biomass oxidation, etc.) to valuable chemicals.